Effect of Organic Fertilizer Type and Nitrogen Fertilizer Dosage on Growth and Yield of Lettuce (Lactuca sativa L.) - Rachman, Aulia; Sondari, Nunung; Ria, Elly Roosma (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
This study aims to study the effect of organic fertilizer application and optimal nitrogen fertilizer dosage on the growth and yield of lettuce plants (Lactuca sativa L.). The research was carried out in Medankarya Village, Tirtajaya District, Karawang Regency from September to October 2019. The research method used was an experiment using Split Plot Design. There were 12 treatments that were repeated 3 times each. The main plot is a type of organic fertilizer (p) consisting of 3 types, namely: p1 = cow manure, p2 = goat manure, and p3 = chicken manure. Meanwhile, the plot is a dose of nitrogen fertilizer (n) consisting of 4 levels, namely: n0 = 0 Kg/ha-1, n1 = 50 Kg/ha-1, n2 = 100 Kg/ha-1 and n3 = 150 Kg/ha-1. The results showed that there was an interaction between the type of organic fertilizer and the dose of nitrogen fertilizer on the height of plants aged 28 days after planting and the leaf area index. The type of cow manure organic fertilizer and nitrogen dose of 100 Kg/ha-1 gave the highest yield in wet weight per plant on lettuce of 79.26 g